Microstructure and Abrasive Wear Resistance of Mo2C Doped Binderless Cemented Carbide - Zan, Xiuqi; Shi, Kaihua; Dong, Kailin; Shu, Jun; Liao, Jun (Frontiers in Materials, 2020)
Binderless cemented carbide contains very little (<0.5 wt.%) or no metal binder and has an incomparable excellent wear resistance, corrosion resistance, excellent polishing, and oxidation resistance compare to traditional cemented carbide (Imasato et al., 1995). For now, many studies were focusing on the influence of Mo/Mo2C on the microstructure and mechanical properties of traditional cemented carbide (Guo et al., 2008; Wang et al., 2010; Yu et al., 2015). However, to our knowledge, no report was found studying on Mo/Mo2C added binderless cemented carbide. In this work, a series of binderless cemented carbides with diverse Mo2C addition amounts (0–6 wt.%) were prepared by sintering and then hot isostatic pressing (HIP) at 2000°C under an isostatic pressure of 70 MPa. The microstructure and abrasive wear resistance of the obtained samples were systemically investigated. The grain size does not change with the increase of Mo2C addition amount, while the abrasive wear resistance of the cemented carbide increases obviously. The data of the abrasive wear test show the wear volume loss of the cemented carbide reduces from 7.32 to 0.02 cm3/105r when the Mo2C addition amount change from 0 to 6.0 wt.%. The superior abrasion resistance of samples with higher Mo2C content and the smoother appearance of the worn surfaces with no definite pullout of grains compared with other samples were result from the forming of (W,Mo)C because of the intermixing between WC and Mo2C caused by high temperature sintering.